(untitled) (Praxis Educativa, 2026)
Hornero Migratorio is a collective songwriting project with audiovisual documentation, exploring and discovering insights beyond mere experiences and outcomes. Conceived from artistic concerns, it evolved into understanding each creative process as a platform of possibilities linked to education beyond the purely artistic realm. The ongoing pursuit of collective learning and its transfer to the communities involved in each process has been the source of numerous practices and dialogues. Engagement with the concept of Art as Education led to the systematization of Hornero Migratorio’s methodology and foundations. Ventana Creativa (Creative Window) is the resulting project, employing two action tools: the Crisálida Creative Education Seminar and the Resortes de Educación Creativa (Creative Education Springs). The latter comprises pedagogical processes, collective creative experiences, and the subjectification of learning within specific contexts. This work aims to historicize and reflect upon this process, considering it from, within, and towards teaching practices that border on the curriculum.